Entrepreneurship attributes that help to develop photography graduates as entrepreneurs / Nur Akma Halili ... [et. al] - Nur Akma, Halili; Nurul Shima, Taharuddin; Mohamad Azlan, Mohamed Amin; Mustafa Halabi, Azahari (Universiti Teknologi MARA, Perak, 2018)
This study focuses on the involvement of photography graduates in commercial photography entrepreneurship or photography business. In the 10th Malaysian Plan, one of the government strategies has put target to transform Malaysia into high income nation. It is therefore, education through higher learning institutions particular young graduates is the targeted group to fulfill this strategy. This includes UiTM particularly photography graduates who have good potential to involve themselves in various photographic businesses. The objectives of this study are to investigate how many photography graduates who have involve in photographic businesses; and to analyse why the numbers of graduates are not interested in photographic entrepreneurship. The two main methods will be employed in this study: questionnaire and interview in obtaining relevant data and information to selected graduates, lecturers as well as graduates who have succeed in photography entrepreneurship. The significance of this the study will help to improve the current photography curriculum as well as to become guidelines for lecturers and current students to involve in photography entrepreneurship. Directly, it will help to government aspiration to become as a high-income nation.